AS IF NOTHING HAD HAPPENED”? KARL BARTH AND THE STUDY OF PROPHETIC PREACHING IN SOUTH AFRICA TODAY - Martin Laubscher (Acta Theologica)
This article explores the significance of Karl Barth’s (homiletical) theology for the current study of prophetic preaching in South Africa today. In the first section, I explore and probe the significance in questioning the current study of prophetic preaching in South Africa, and whether one could relate that to the call of reading Barth’s theology anew in the South African context. Thereafter, I explore both these focuses in more detail in their own right – the state of discourse and scholarship in our study of prophetic preaching, and the significance of revisiting and exploring the meaning in Barth’s famous words to do (in the midst of crises) theology “as if nothing had happened”. In the last section, I will spell out some of these insights of Barth for the study and practice of prophetic preaching in South Africa today.